Antimicrobial properties of local honey against pathogenic wound causing bacteria in animals - Mussafeer, Jiavendrasingh (2015)
Honey has been used for medicinal purposes since the times of ancient civilisations because of its known antimicrobial, anti-inflammatory and healing properties. This study aimed to investigate the antimicrobial properties of local Malaysian honey against common pathogenic wound associated bacteria in animals. Five types of honey which comprised of local honey; Kelulut, multifloral, Propolis, artificial and imported honey; Manuka, were tested for their antibacterial activity against eight bacteria among which four were Gram positive (Methicillin Resistant Staphylococcus aureus (MRSA), Vancomycin Resistant Enterococci (VRE), Bacillus subtilis and Staphylococcus intermedius and four were Gram negative bacteria (Proteus mirabilis, E.coli, Pseudomonas aeruginosa and Pasturella multocida). The well diffusion method was performed to screen pure undiluted honeys against bacteria, and the zones of inhibition were measured. The Minimum Inhibitory Concentration (MIC) for each honey was then determined using the microbroth dilution method. The most susceptible bacteria was P. multocida (mean inhibition zone of (20.96 ± 3.56) mm in diameter), compared to P. mirabilis (5.71 ± 3.86) mm), being the least susceptible. There was a significant difference among the types of honey and the inhibition zone (p<0.05), with the most effective honey being Manuka, followed by Propolis, kelulut, Multifloral and lastly artificial honey. Minimum inhibition concentration results revealed that Kelulut was the most effective honey with mean MIC of (18.13 ± 5.82) %, followed by Propolis (31.25 ± 8.44) %, Manuka (34.38 ± 9.38) % and lastly artificial honey (34.38 ± 9.38) %. Polyfloral honey barely inhibited bacteria when diluted. It was noted that few of the honeys which are not efficient in pure form were effective when diluted. This may due to the release and action of hydrogen peroxide when the honeys are diluted. In conclusion, Malaysian honey (Kelulut, Multifloral, Propolis) do possess antimicrobial properties against important pathogens and has the potential to be used for wound treatment.